2020
DOI: 10.3390/ijms21249476
|View full text |Cite
|
Sign up to set email alerts
|

ROS and Ions in Cell Signaling during Sexual Plant Reproduction

Abstract: Pollen grain is a unique haploid organism characterized by two key physiological processes: activation of metabolism upon exiting dormancy and polar tube growth. In gymnosperms and flowering plants, these processes occur in different time frames and exhibit important features; identification of similarities and differences is still in the active phase. In angiosperms, the growth of male gametophyte is directed and controlled by its microenvironment, while in gymnosperms it is relatively autonomous. Recent revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 82 publications
0
19
0
Order By: Relevance
“…Scission of polysaccharides via the function of OH− results in loosing of pollen wall, probably leading to the acceleration of pollen hydration [ 69 ]. In contrast, H 2 O 2 strengthens polymers via peroxidase-mediated cross-linking of hydroxycinnamates [ 44 , 70 ]. In Arabidopsis, KINβγ is known as a subunit of SUCROSE NON-FERMENTING 1-RELATED PROTEIN KINASE 1 (SnRK1) complex that is essential for maintenance of the functions of the mitochondria and peroxisomes [ 71 ].…”
Section: Pollen Adhesion and Hydrationmentioning
confidence: 99%
See 2 more Smart Citations
“…Scission of polysaccharides via the function of OH− results in loosing of pollen wall, probably leading to the acceleration of pollen hydration [ 69 ]. In contrast, H 2 O 2 strengthens polymers via peroxidase-mediated cross-linking of hydroxycinnamates [ 44 , 70 ]. In Arabidopsis, KINβγ is known as a subunit of SUCROSE NON-FERMENTING 1-RELATED PROTEIN KINASE 1 (SnRK1) complex that is essential for maintenance of the functions of the mitochondria and peroxisomes [ 71 ].…”
Section: Pollen Adhesion and Hydrationmentioning
confidence: 99%
“…High accumulation of ROS in the stigma prior to the pollen attachment was proposed to be essential for pollen–pistil interaction, as well as defense mechanisms against microbe attack [ 17 , 44 , 75 ]. Decreased level of ROS in the stigma by the exogenous application of flavonoids inhibited the attachment of pollen to the stigma [ 76 ], suggesting the significance of high level of ROS accumulation in the stigma for pollen adhesion.…”
Section: Pollen Adhesion and Hydrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Redox homeostasis is one of the main regulatory systems during pollen germination and tube growth in flowering plants, and it has been actively studied in recent years, especially regarding pollination and pollen behavior in vivo [ 89 , 90 , 91 , 92 ]. However, much less is known about the role of this system in gymnosperms [ 89 ]. For example, ROS can affect the germination pattern in Picea pungens , altering rigidity of the cell wall and its resistance to rupture [ 31 ].…”
Section: Biochemical Regulation Of Conifer Pollen Germination and Pollen Tube Growthmentioning
confidence: 99%
“…ROS are a universal regulatory element in plant cells and participate in an array of signaling pathways. Breygina and Klimenko reviewed the role of ROS and the underlying mechanism involving ion transport systems during plant sexual reproduction [ 17 ]. They found that ROS are involved at most stages of the life cycle in the male gametophyte, and it chiefly acts through ion currents by a feedback loop.…”
mentioning
confidence: 99%